Characteristics of participants in a public rubella antibody testing program conducted at a Japan professional football league venue - Toshinori Nishizawa; Kuniyoshi Hayashi; Noriyuki Amano; Gautam A. Deshpande; Hiroko Arioka (Journal of General and Family Medicine)
Abstract Background Hypothesizing that soccer‐associated public health campaigns influence men more than women, we investigated the characteristics and motivations of participants who received rubella antibody testing at a Japanese professional football league event. Methods This was a survey‐based cross sectional study, comparing the characteristics and motivations between men and women regarding rubella antibody testing. Results Free and convenient testing was the biggest behavioral influencer, but the information provided by healthcare professionals and athletes also played a strong motivating role. Men reported more influence from celebrity athletes than women. Conclusions Public health attention raised by celebrity athletes may facilitate rubella awareness among male spectators.